INTERPRETASI HISTORIS KRISTIS TERHADAP BEHEMOT DAN LEVIATAN DALAM KITAB AYUB 40:10-28 DAN RELEVANSINYA BAGI ORANG PERCAYA MASA KINI - Ezra Azriel lado’; Vertika Chrisma Malino; Imel Sakke (Adisam Publisher, 2026)
The Book of Job is one of the wisdom books in the Old Testament that profoundly discusses the reality of human suffering and the sovereignty of God. In the final section of this book, particularly in Job chapters 40–41, God describes two powerful and mysterious creatures, namely Behemoth and Leviathan. The descriptions of these creatures have given rise to various interpretations among biblical scholars. This study aims to interpret Behemoth and Leviathan in Job 40:10–28 using a historical-critical approach and to examine their relevance for the lives of believers today. The historical-critical method is employed to understand the text based on its historical background, the culture of the Ancient Near East, and the literary context of the Book of Job. The results of this study indicate that Behemoth and Leviathan not only represent large and powerful physical creatures, but also symbolize natural forces that cannot be controlled by humans. Through these depictions, God affirms that all creation is under His sovereignty. For contemporary believers, this passage teaches the importance of humility, recognition of human limitations, and trust in God’s sovereignty in facing suffering and various life struggles.